2019
DOI: 10.3389/fonc.2019.01391
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Serum EB Virus Zta Antibody in the Diagnostic of Nasopharyngeal Carcinoma: Evidences From 2,126 Cases and 15,644 Controls

Abstract: We collected previous published data and performed a systematical assessment for the diagnostic value of serum Zta antibody in NPC patients. Using bivariate-mixed effect model, we calculated the sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnosis odds ratio (DOR), and summary receiver operating characteristics curve (AUC) and their 95% confidence intervals (CIs). We also performed subgroup analysis to explore the heterogeneity. We included 23 studies including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…High anti-ZEBRA IgG titers in sera correlate with poorer clinical outcome in patients [99,100]. The presence of anti-ZEBRA antibody has a high diagnostic accuracy for early-stage NPC [101]. More generally, EBV replication and expression of some early lytic cycle genes were detected in EBV-induced epithelial malignancies including NPC [102,103].…”
Section: Zebra Implication In Ebv-related Malignanciesmentioning
confidence: 99%
“…High anti-ZEBRA IgG titers in sera correlate with poorer clinical outcome in patients [99,100]. The presence of anti-ZEBRA antibody has a high diagnostic accuracy for early-stage NPC [101]. More generally, EBV replication and expression of some early lytic cycle genes were detected in EBV-induced epithelial malignancies including NPC [102,103].…”
Section: Zebra Implication In Ebv-related Malignanciesmentioning
confidence: 99%
“…Recent studies in NPC patients have identified antibodies against EBV antigens, including early antigen (EA), viral capsid antigen (VCA) and Epstein–Barr virus nuclear antigen 1 (EBNA1) [ 25 ]. When EBV enters the lytic cycle, Rta and Zta are encoded and then EA is encoded [ 26 ]. At the end of the EBV proliferation cycle, VCA is expressed.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18]28,29 In addition, a recent meta-analysis including 2,126 NPC patients and 15,644 controls showed that serum EBV Zta antibody exhibited a high diagnostic accuracy with a sensitivity of 0.85, a specificity of 0.9 and an AUC of 0.94 for NPC. 30 Nevertheless, serum EBV Zta antibody is not popular for the identification of NPC in clinical practices. 31 Heat shock protein (HSP), also termed stress protein, is a class of proteins that are highly expressed in cells in response to physicochemical stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Our data demonstrate that both EBV DNA and plasma HSP90α exhibit higher performance for the diagnosis of NPC than serum EBV VCA IgA antibody, which was in agreement with previous studies reporting a higher diagnostic efficacy of EBV DNA than serum EBV VCA IgA antibody for NPC. 54 In addition, serum EBV Zta antibody was also found to present a high diagnostic accuracy for NPC 30 ; however, there have been no comparisons of the performance between plasma HSP90α and serum EBV Zta antibody for the diagnosis of NPC until now. Previous studies have shown that the combination of multiple biomarkers may increase the detection of cancers.…”
mentioning
confidence: 99%